Hungarian Monitoring, 5 February 1988 . [Magyar rádiófigyelő], 1988. február 5 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Official rehabilitation of Bukharin - Gorbachev and Reagan nominated for 1988 Nobel Peace Prize - Carlucci in Bonn - Human rights conference in Venice Domestic Affairs: - André Erdős on taking responsibility for Hungarians outside the borders - 'Friendship 88' military training comes to an end - Debate on atomic waste - Two theaters in dispute over authors' plagiarism case Economy: - Hungarian National Bank restricts loan opportunities - Large number of artisans return their operating licenses - Sino-Hungarian, Hungarian-Far Eastern trade relations - Factory directors: industry and environment protection at Inota aluminum forge Külpolitika: - Buharin hivatalos rehabilitációja - Gorbacsov és Reagan mint a 88-as béke Nobel - Díj jelöltjei - Carlucci Bonnban - Velencei emberi jogi tanácskozás Belpolitika: - Erdős André a határon túli magyarokért való felelősségvállalásról a velencei tanácskozáson - Befejeződött a Barátság 88' hadgyakorlat - Vita az atomhulladék-tároló ügyéről - Viszály két színház között: plágiumperre készülnek a szerzők Gazdaság: - Az MNB szűkítette a hitelfelvétel lehetőségeit - Nagy számban adják vissza kisiparosok iparengedélyüket - Magyar-kínai, magyar-távol-keleti gazdasági kapcsolatok - Ipargazdák: ipar és környezetvédelem kapcsolata - Az Inotai Alumíniumkohó